A safe sanctuary away from home: Working women’s perceptions of power, gender-based violence and HIV-infection risk within intimate relationships - Freeman, Rachel J.; Kamwanyah, Ndumba J. (Journal for Studies in Humanities and Social Sciences, 2015)
In this manuscript insight about working women’s perceptions of power, gender-based violence and HIV-infection risk within intimate relationships in an airline business is provided. The manuscript is based on the findings from a Master of Arts thesis conducted by Ms Rachel Free man, the main author of this article, in an airline business in Windhoek. Qualitative in design, in-depth face-to-face interviews were conducted with five women employees in an airline business to explore their experience and perceptions of power, gender-based violence and the risk of HIV-infection risk. Such insights formed the backdrop to data gathering, which used a narrative approach in which women were asked to retell their experiences of power, gender-based violence and HIV-infection risk within their intimate relationships, including the significance of the presence of an employee Assistance Program (EAP) in their lives as employees of an airline business; therefore providing them a safe sanctuary away from the chaos of their home environment. This manuscript covers a brief introduction of the study; the aim and objectives; it explores the extent of the problem being investigated; it provides a theoretical perspective as well as looking at the methodology of the study; and data analysis. The manuscript concludes with specific recommendations about the relevancy and importance of work place programmes to protecting and promoting women’s wellbeing and rights.